Effectiveness of Distribution Zakat Infaq Sedekah Funds To Improve Mustahik Education Stages Through Achieving Orphans Scholarship Program At Yatim Mandiri Jombang - Lailatul Fitriyah Fitriyah; Ahmad Supriyadi (Profesional Muda Cendekia Publishing, 2022)
This research is a field research that uses a descriptive qualitative approach, which in this study describes the effectiveness of the distribution of zakat infaq and alms funds to increase the level of mustahik educators through the achievement orphan scholarship program at the Mandiri Jombang orphanage. Data obtained by researchers through direct interview observations from informants and documentation. for the data that has been collected then analyzed through 3 stages, namely data redaction, data exposure and drawing conclusions. The distribution of alms infaq funds at the Mandiri orphanage in Jombang Regency in the achievement orphan scholarship program is fairly good because this institution has used the zakat infaq alms funds properly. Namely, by distributing zakat infaq alms funds on the basis of the educational welfare of poor orphans and their distribution has been achieved on the target of distributing zakat infaq and alms funds, it is quite effective in improving the welfare of mustahik through the orphan scholarship program, the achievements of the Independent Orphan Institute, Jombang Regency, which can be seen from the satisfaction parents who feel that their economy has been helped by the help of this program. the second is the number of orphans who have completed their education. The third is that many of them are helped by the additional learning system that is carried out in each of the closest studios, so that orphans and needy people feel helped if there are difficulties regarding learning at school. Lessons in the studio are held four times a week.